Money Mastery: Elevating Your Financial Competence in a Fast-paced World - Linda Ayu Oktoriza; Amimah Qodari; Vera Sari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research investigates the intricate relationships between financial education, technology utilization, financial behavior, and financial competence among customers of Bank BCA Tembalang. Utilizing a quantitative research design and employing random sampling, data was collected from 70 bank customers. Path analysis using SmartPLS was conducted to examine direct and indirect effects. The results reveal significant direct effects of financial education and technology utilization on financial competence, as well as significant indirect effects through financial behavior. Financial education emerges as a key driver in shaping positive financial behaviors and enhancing financial competence, while the utilization of financial technology also plays a significant role. These findings underscore the importance of targeted educational initiatives and the adoption of digital financial tools in promoting financial literacy and empowering individuals to make informed financial decisions. Ultimately, this research contributes to the advancement of strategies aimed at improving financial well-being and service efficiency within the banking sector.